2021
DOI: 10.1155/2021/6691724
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Nonlinear Grey Bernoulli Model Based on the Whale Optimization Algorithm and Its Application

Abstract: In order to improve the prediction performance of the existing nonlinear grey Bernoulli model and extend its applicable range, an improved nonlinear grey Bernoulli model is presented by using a grey modeling technique and optimization methods. First, the traditional whitening equation of nonlinear grey Bernoulli model is transformed into its linear formulae. Second, improved structural parameters of the model are proposed to eliminate the inherent error caused by the leap jumping from the differential equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…To avoid inherent errors, an improved nonlinear grey Bernoulli model was obtained. Results indicated that the prediction accuracy of this model was higher, and it was more suitable for these practical situations [9]. Tian et al proposed a new data-driven model to improve process data modeling accuracy.…”
Section: Related Workmentioning
confidence: 98%
“…To avoid inherent errors, an improved nonlinear grey Bernoulli model was obtained. Results indicated that the prediction accuracy of this model was higher, and it was more suitable for these practical situations [9]. Tian et al proposed a new data-driven model to improve process data modeling accuracy.…”
Section: Related Workmentioning
confidence: 98%
“…Firstly, we compare the optimization algorithms. The results of OBLAOA are compared with the following algorithms: Arithmetic Optimization Algorithm (AOA), Whale Optimization Algorithm (WOA) [45], Salp Swarm Algorithm (SSA) [46], Weighted Salp Swarm Algorithms (WSSA) [47], Exponential Neighborhood Grey Wolf Optimization (ENGWO) [48], developed Arithmetic Optimization Algorithm (dAOA) [49] and improved arithmetic optimization algorithm (IAOA) [50]. Secondly, we compare our OBLAOA-DBSCAN algorithm with five classical clustering algorithms, namely K-means [51], Spectral [52], OPTICS [53], clustering by fast search and find of density peaks (DPC) [54] and the original DBSCAN.…”
Section: Experiments Settingsmentioning
confidence: 99%
“…The conditional independence of the Naive Bayes classifier limits the scope of application and classification accuracy of the Naive Bayes classification. The conditional independence of naïve Bayes classifier limits the scope of application and classification accuracy of naïve Bayes classification, Jiang Liqing et al [16] proposed to use of an improved whale optimization algorithm to optimize the naïve Bayes classifier, and the improved whale optimization algorithm uses a taboo search mechanism to jump out of the error that the algorithm is prone to fall into local optimization when the algorithm seeks optimization, and the algorithm automatically searches the global weights of the attributes of the classifier, thereby improving the accuracy of the weighted Bayesian classifier operation. Tan Zhang et al [17] based on the three existing classifier evaluation indicators of accuracy, recall rate, and F1-score, a new classifier evaluation index is designed, and through the classification experiment based on CNN and RNN classifiers, compared with the different performances of new and old indicators in the performance evaluation of classifiers, the results show that the evaluation of the classification results of the new indicators is more comprehensive, but the applicability of the new indicators to the classification of unbalanced data sets can be further improved.…”
Section: Introductionmentioning
confidence: 99%